Acclimation to Nutritional Immunity and Metal Intoxication Requires Zinc, Manganese, and Copper Homeostasis in the Pathogenic Neisseriae - Branch, Alexis Hope; Stoudenmire, Julie L.; Seib, Kate L.; Cornelissen, Cynthia Nau (Frontiers in Cellular and Infection Microbiology, 2022)
Neisseria gonorrhoeae and Neisseria meningitidis are human-specific pathogens in the Neisseriaceae family that can cause devastating diseases. Although both species inhabit mucosal surfaces, they cause dramatically different diseases. Despite this, they have evolved similar mechanisms to survive and thrive in a metal-restricted host. The human host restricts, or overloads, the bacterial metal nutrient supply within host cell niches to limit pathogenesis and disease progression. Thus, the pathogenic Neisseria require appropriate metal homeostasis mechanisms to acclimate to such a hostile and ever-changing host environment. This review discusses the mechanisms by which the host allocates and alters zinc, manganese, and copper levels and the ability of the pathogenic Neisseria to sense and respond to such alterations. This review will also discuss integrated metal homeostasis in N. gonorrhoeae and the significance of investigating metal interplay.